The association between anticoagulation therapy, maternal characteristics, and a failed cfDNA test due to a low fetal fraction. (6th October 2017) - Burns, Whitney; Koelper, Nathanael; Barberio, Andrea; Deagostino‐Kelly, Mary; Mennuti, Michael; Sammel, Mary D.; Dugoff, Lorraine
Abstract: Objectives: The objective of this study was to identify maternal characteristics associated with a failed cell‐free DNA (cfDNA) test due to a low fetal fraction (FF). Method: Retrospective cohort study of women with singleton pregnancies who had cfDNA screening at 10–25 weeks gestation between October 2011 and January 2016. cfDNA screening was performed using methylation techniques until October 2013; thereafter, samples were run with massively parallel sequencing. Multivariable logistic regression was performed to identify maternal characteristics associated with no cell free DNA result secondary to low FF. Results: Thirty‐three (1.2%) of 2890 eligible women had a failed cfDNA test, including 18 (0.6%) cases with a low FF. A failed cfDNA test due to a low FF was associated with obesity (aOR 1.11, CI 1.05–1.18, p  = 0.0003) and treatment with enoxaparin (aOR 37.5, 11.19–125.87, p  < 0.0001). 5 of 28 (18%, 95% CI: 6.1%–36.9%) women on enoxaparin had a failed cfDNA test secondary to a low FFx. Conclusion: Enoxaparin therapy and obesity were associated with an increased incidence of a failed cfDNA test due to low FF. Further research is needed to determine the mechanism by which anticoagulation therapy alters cfDNA test functionality and identify approaches to improve test performance in these women. Abstract : What's already known about this topic? A low fetal fraction may result in a failed cell free DNA test; obesity, early gestational age, maternal hypertension, and fetal aneuploidy are associated with a low fetal fraction What does this study add? This is a large retrospective study confirming the effect of obesity on fetal fraction and identifying a significant effect of enoxaparin therapy on fetal fraction.